TINDAK TUTUR ILOKUSI TIDAK LANGSUNG DALAM ANIME BUNGOU STRAY DOGS - Hamidah Nur Permata; Anisa Arianingsih (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This study aims to describe the meaning of indirect directive illocutionary speech acts in Bungou Stray Dogs anime. The method used in this study is a descriptive method with a note-taking technique. The core theory in this study is Austin's speech act theory and Saifudin's indirect illocutionary theory. The data were analyzed based on the Namatame’s theory to classify the meaning of indirect directive illocutionary speech acts. From the results of the study, there were 4 meaning of the indirect directive illocutionary speech act in Bungou Stray Dogs anime. There were commanding meaning that is utteranced implicitly using declarative sentences, requests meaning that is utteranced implicitly using declarative and interrogative sentences, prohibitions meaning that is utteranced implicitly using declarative and interrogative sentences, and suggestions meaning that is utteranced implicitly using declarative sentences. Keywords: Indirect speech act, Directive speech act, Perlocutionary